Barium titanate-based multilayer composite wave-absorbing material and preparation method thereof
Patent Information
- Application Number
- CN202410091713.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-23
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-23
AI Technical Summary
[0010]虽然通过调控形貌以及掺杂改性可以提升高介电损耗BaTiO3铁电材料的吸波性能,但是这些相关工作中存在以下问题:1)各种复合材料多为颗粒之间的点接触,接触面积小,并且粉体团聚严重;2)通常,只简单的利用了复合材料的介电损耗和磁损耗,没有很好利用多种耦合损耗,从而没有达到真正的复合效果;3)有效吸收带宽较窄;4)厚度较高,难以轻量化
[0048](1)本发明使用简单的两步水热法制备负载Fe3O4的BaTiO3多层纳米复合材料,其中BaTiO3粉体粒径小,平均粒径在110nm左右,分散性良好,是制备复合吸波材料的优异基体。
Smart Images

Figure CN117939867B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing materials technology, and particularly relates to a barium titanate-based multilayer composite wave absorbing material and its preparation method. Background Technology
[0002] In recent years, the development and widespread use of various electronic devices have brought great convenience to people's lives and work. At the same time, the resulting electromagnetic radiation and interference not only affect the normal operation of electronic devices but also endanger people's health, becoming another significant and difficult-to-protect source of pollution after noise pollution, air pollution, water pollution, and solid waste pollution. Electromagnetic absorbing materials technology, as a commonly used method for combating electromagnetic pollution, has received widespread attention.
[0003] Currently, microwave absorbing materials face high standards of being "thin, light, wide, and strong." Generally speaking, an ideal microwave absorbing material needs to meet two conditions: first, it must have good impedance matching so that incident electromagnetic waves can be absorbed into the material to the maximum extent; second, it must dissipate the energy of the incident electromagnetic waves in a certain way. However, traditional single-phase microwave absorbing materials often face difficulties such as narrow absorption bandwidth and thick matching thickness due to poor impedance matching and a single attenuation mechanism.
[0004] Recent studies have shown that composite materials containing both magnetic and dielectric losses are an effective strategy for improving the microwave absorption performance of materials. They can effectively improve impedance matching and attenuation characteristics, thereby enhancing absorption performance through the synergistic effect of dielectric and magnetic losses. Xu et al. used a multi-component glass of BaO-TiO2-B2O3-Na2O-SiO2-Al2O3-Fe2O3, and then annealed it to achieve in-situ precipitation of BaTiO3 and BaFe in the glass matrix. 12 O 19 Phase, when BaTiO3 and BaFe 12 O 19 With a content ratio of 3:2, it exhibits optimal impedance matching and significant electromagnetic attenuation: the reflection loss is as low as -44.5 dB at 3.7 GHz, and the effective absorption bandwidth is 3.93 GHz with a thickness of 2 mm. Its excellent absorption performance is attributed to the BaFe content in the glass matrix. 12 O 19 / BaTiO3 / BaFe 12 O 19 Abundant heterostructures generated by stacking mode (Tailoring electromagnetic wave absorption using in-situ precipitation of BaTiO3-BaFe) 12 O 19glass ceramic,Ceramics International,2024,50(2):3119-3128.).
[0005] Mandal et al. successfully synthesized Ni using a simple electrospinning method. 0.4 Co 0.2 Zn 0.4 Multiferroic composite fibers composed of Fe2O4 (NCZFO) spinel ferrite and BaTiO3 (BTO) effectively achieve weight reduction, with a minimum reflection loss of -42.53 dB at 11.81 GHz. Furthermore, the electromagnetic parameters and microwave absorption performance can be easily and effectively adjusted by controlling the molar ratio of the two phases (Mandal A, Das C K. Effect of BaTiO3 on the microwave absorbing properties of Co-doped Ni-Zn ferrite nanocomposites, Journal of Applied Polymer Science, 2014, 131(4). 39926, https: / / doi.org / 10.1002 / app.39926).
[0006] Chen et al. successfully prepared porous core-shell Fe3O4 / SnO2 nanorods using a two-step hydrothermal method. At a thickness of 2 mm, the maximum reflection loss was -27.9 dB. The excellent microwave absorption performance was attributed to the effective complementarity between dielectric loss and magnetic loss, as well as the special core-shell structure (Chen YJ, Gao P, Wang RX, et al. Porous Fe3O4 / SnO2 core / shell nanorods: synthesis and electromagnetic properties, The Journal of Physical Chemistry C, 2009, 113(23): 10061-10064.).
[0007] Wang et al. successfully prepared Fe3O4 / ZnO heterostructure microwave absorbing material by growing Fe3O4 nanocrystals on ZnO nanosheets. The material had the lowest reflection loss of -22.69 dB and an effective absorption bandwidth of 5.89 GHz (Wang Z, Wu L, Zhou J, et al. Enhanced microwave absorption of Fe3O4 nanocrystals after heterogeneously growing with ZnO nanoshell, RSC advances, 2013, 3(10): 3309-3315.).
[0008] Dong et al. synthesized NiFe2O4 and ZnO particles by co-precipitation and wet chemical chemiluminescence, respectively. Then, they mixed NiFe2O4 and ZnO particles in different proportions, pressed them into tablets, annealed them, ground them into powder, and mixed them with paraffin to test their microwave absorption performance. Among them, the 0.7NiFe2O4-0.3ZnO sample had the lowest reflection loss of -20dB at 5.5GHz. However, unfortunately, its effective absorption bandwidth was almost 0GHz at a thickness of 3mm (Dong C, Zheng X, Li J, et al. Enhanced microwave magnetic properties of Niferrite doped ZnO, IEEE transactions on magnetics, 2013, 49(7):4238-4241.).
[0009] The patent "Preparation Method of High-Absorption Nano-Barium Titanate / Fe3O4 Hybrid Material" (ZL202110736189.0) first synthesizes BaTiO3 powder with a particle size of 10nm-500nm, and then anneals the BaTiO3 powder at 300-800℃ for 2-4 hours. Next, a small amount of solvent is added to the BaTiO3 powder and ground into a slurry, which is then mixed with NaOH solution. Fe source solution is added dropwise to the BaTiO3 powder slurry through a burette to carry out the hybridization reaction, finally obtaining a high-absorption nano-barium titanate / Fe3O4 (BaTiO3 / Fe3O4) hybrid material powder. When the thickness of the hybrid material is 2mm, the reflectivity at 2GHz can reach -9.84 to -29.4dB, showing promise for use in microwave absorbing coatings or electromagnetic shielding materials.
[0010] While the microwave absorption performance of high-dielectric-loss BaTiO3 ferroelectric materials can be improved through morphology control and doping modification, these related works suffer from the following problems: 1) Most composite materials involve point contacts between particles, resulting in small contact areas and severe powder agglomeration; 2) Typically, only the dielectric and magnetic losses of the composite materials are utilized, without effectively leveraging multiple coupling losses, thus failing to achieve a true composite effect; 3) The effective absorption bandwidth is relatively narrow; 4) The thickness is significant, making lightweighting difficult. These problems make it difficult for existing materials to meet the current requirements for microwave absorbing materials to be "thin, light, wide, and strong." Summary of the Invention
[0011] To address the aforementioned technical problems, this invention proposes a barium titanate-based multilayer composite microwave absorbing material and its preparation method.
[0012] To achieve the above objectives, the present invention provides the following technical solution:
[0013] One of the technical solutions of the present invention:
[0014] A method for preparing a barium titanate-based multilayer composite microwave absorbing material involves using BaCl2·2H2O as the barium source, TiCl4 as the titanium source, and NaOH as the mineralizing agent to prepare barium titanate (BaTiO3) nanopowder via a hydrothermal method. The BaTiO3 nanopowder is then mixed with FeCl3·6H2O and anhydrous sodium acetate (NaAc) to prepare the barium titanate-based multilayer composite microwave absorbing material (BaTiO3 / Fe3O4 composite microwave absorbing material) via a hydrothermal method.
[0015] Multiferroic composite materials possess ferroelectricity, ferromagnetism, and magnetoelectric coupling effects, exhibiting greater application potential in microwave absorption compared to single-phase absorbing materials. Their superior absorption performance stems from enhanced interfacial polarization and the synergistic effect of magnetic and electrical losses. The multilayer structure of ferroelectric and ferromagnetic materials can significantly increase the interface and form a heterogeneous structure, thereby substantially improving absorption performance. Based on this, this invention employs a simple and economical two-step hydrothermal method. By loading ferrite Fe3O4 onto BaTiO3 particles to construct a ferrite-air-ferroelectric multilayer structure, the interface is increased while simultaneously forming a heterogeneous structure, significantly enhancing interfacial polarization. This achieves a synergistic effect between semiconductor electrical losses, ferromagnetic magnetic losses, and ferroelectric dielectric losses, resulting in excellent microwave absorption performance. This invention also adjusts the ratio of the two components to obtain different multilayer structures, thereby regulating the electromagnetic parameters of the absorbing material and preparing high-performance composite absorbing materials to meet the requirements of "thin, light, wide, and strong" absorbing materials.
[0016] Furthermore, the preparation method of the barium titanate-based composite microwave absorbing material includes the following steps:
[0017] (1) Using BaCl2·2H2O (barium chloride dihydrate) as the barium source, TiCl4 (titanium tetrachloride) as the titanium source, and NaOH (sodium hydroxide) as the mineralizing agent, the precursor solution was obtained by mixing and dissolving it thoroughly in deionized water.
[0018] (2) The precursor solution was subjected to a first hydrothermal reaction. After the reaction was completed, the solution was naturally cooled and then centrifuged, washed and dried to obtain barium titanate nanopowder.
[0019] (3) The barium titanate nanopowder was ultrasonically dispersed in ethylene glycol, and then FeCl3·6H2O (ferric chloride hexahydrate) and anhydrous NaAc were added and stirred to obtain a yellowish-brown solution;
[0020] (4) The yellowish-brown solution is subjected to a second hydrothermal reaction. After the reaction is completed, the solution is naturally cooled, and after centrifugation, washing and drying, barium titanate-based composite microwave absorbing material is obtained.
[0021] Further, in step (1), the molar ratio of BaCl2·2H2O to TiCl4 is 1.5∶1; the concentration of NaOH in the precursor solution is 2M.
[0022] Further, in step (2), the first hydrothermal reaction is carried out in a reactor, the filling degree of the reactor is 60-80%, the temperature of the first hydrothermal reaction is 210°C, and the time is 24h.
[0023] Furthermore, in step (2), the centrifugation is performed in a centrifuge with a rotation speed of 7000-9000 rpm for 2-3 minutes;
[0024] The washing process involves sequentially washing with dilute acetic acid, deionized water, and ethanol, wherein the concentration of the dilute acetic acid is 3M.
[0025] The drying process involves drying in an oven at 70°C for 12 hours.
[0026] Furthermore, in step (3), the ultrasonic time is 30 min; the stirring time after adding FeCl3·6H2O and anhydrous NaAc is 30 min.
[0027] Further, in step (3), the BaTiO3 nanopowder and the FeCl3·6H2O are mixed in the form of (1-x)BaTiO3-xFe3O4, where 0.25≤x≤0.75, that is, the total amount of BaTiO3 and Fe3O4 is 1, and x is the molar content of Fe3O4. For example, if x=0.25, that is, the molar content of Fe3O4 is 25% and BaTiO3 is 75%.
[0028] The principle of this invention:
[0029] 1. In the first step, BaTiO3 nanoparticles are synthesized by hydrothermal method. The BaTiO3 nanoparticles are ultrasonically dispersed in ethylene glycol. In the second step of hydrothermal method, they will become the nucleation center of Fe3O4, resulting in heterogeneous nucleation. The nucleation of Fe3O4 on BaTiO3 nanoparticles not only reduces the surface energy of BaTiO3 powder, but also the nucleation energy of Fe3O4 is relatively low. Therefore, Fe3O4 nucleates and grows on BaTiO3 nanoparticles.
[0030] 2. When the Fe3O4 content is low, it forms a large number of nanoparticles on the surface of BaTiO3 powder. As x increases in the (1-x)BaTiO3-xFe3O4 (0.25≤x≤0.75) composite material, that is, the Fe3O4 content gradually increases, the Fe3O4 nanoparticles on the surface of BaTiO3 powder come into contact with each other and achieve surface contact, forming a Fe3O4 shell on the outside of BaTiO3 powder.
[0031] 3. During the formation of the BaTiO3-Fe3O4 core-shell structure, on the one hand, a small number of Fe ions are doped into the BaTiO3 lattice, thus forming a BaTiO3-Fe3O4 heterostructure; on the other hand, during the hydrothermal process, a thin air layer is formed between the Fe3O4 shell and the BaTiO3 core, thus forming a multilayer structure.
[0032] Further, in step (4), the second hydrothermal reaction is carried out in a reactor, the filling degree of the reactor is 60-80%, the temperature of the second hydrothermal reaction is 200°C, and the time is 8 hours;
[0033] The washing process involves alternating between ethanol and deionized water three times each.
[0034] The drying process involves drying in an oven at 60°C for 12 hours.
[0035] Furthermore, the preparation method of the barium titanate-based composite microwave absorbing material is as follows:
[0036] (1) First, add NaOH and BaCl2·2H2O to deionized water and stir magnetically for 30 min. Then, slowly add TiCl4 and continue stirring for 30 min to obtain the precursor solution. The slow addition is specifically: the addition rate is 1 to 2 drops / second.
[0037] (2) Transfer the precursor solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 210°C for 24 hours to allow it to react fully.
[0038] (3) Wait for the oven to cool naturally, take out the reaction vessel from the oven, pour the solution into the centrifuge tube, wash and centrifuge repeatedly with dilute acetic acid (concentration of 3M), deionized water and alcohol in sequence, centrifuge at a speed of 7000-9000 rpm for 2-3 min, and then dry in an oven at 70℃ for 12 hours to obtain barium titanate nanopowder.
[0039] (4) Add the barium titanate nanopowder obtained in step (3) into ethylene glycol and ultrasonically disperse it for 30 min. Then, according to the chemical formula (1-x)BaTiO3 / xFe3O4, where 0.25≤x≤0.75, add FeCl3·6H2O and anhydrous NaAc and magnetically stir for 30 min at a stirring speed of 500-700 rpm to obtain a yellowish-brown solution.
[0040] (5) Transfer the yellowish-brown solution obtained in step (4) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 200°C for 8 hours to allow it to react fully.
[0041] (6) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge multiple times at a speed of 7000-9000 rpm for 2-3 minutes, wash with ethanol and deionized water three times each during the process, and then dry in an oven at 70°C for 12 hours to obtain BaTiO3 / Fe3O4 composite microwave absorbing material.
[0042] This invention utilizes a simple two-step hydrothermal method to prepare Fe3O4-loaded BaTiO3 nanomaterials. By changing the ratio of Fe3O4 to BaTiO3, the magnetoelectric properties of the composite material can be controlled, resulting in better matching impedance and lower reflection loss. This invention provides a simple and low-cost method for synthesizing barium titanate-based composite microwave absorbing materials. Furthermore, the prepared barium titanate-based composite microwave absorbing material (0.5BaTiO3 / 0.5Fe3O4 composite microwave absorbing material) achieves a minimum reflection loss of -48.1 dB at a thickness of 2.05 mm and a frequency of 13.2 GHz; and an effective absorption bandwidth of 6.3 GHz at a thickness of 1.90 mm.
[0043] The second technical solution of the present invention:
[0044] A barium titanate-based composite microwave absorbing material prepared by the above preparation method.
[0045] The third technical solution of the present invention:
[0046] The barium titanate-based composite absorbing material described herein has applications in stealth aircraft, electromagnetic interference, and radiation protection clothing.
[0047] Compared with the prior art, the present invention has the following advantages and technical effects:
[0048] (1) The present invention uses a simple two-step hydrothermal method to prepare BaTiO3 multilayer nanocomposite material loaded with Fe3O4. The BaTiO3 powder has a small particle size with an average particle size of about 110 nm and good dispersibility, making it an excellent matrix for preparing composite microwave absorbing materials.
[0049] (2) By changing the ratio of Fe3O4 and BaTiO3 to regulate the microstructure of composite materials, a multilayer structure of ferrite (Fe3O4)-air-ferroelectric (BaTiO3) can be constructed, which not only greatly increases the interface, but also forms a heterogeneous structure.
[0050] (3) Abundant Absorption Mechanisms. The Fe3O4-air-BaTiO3 multilayer structure of the composite material not only enables semiconductor-level electrical loss but also significantly increases the ferrite-air-ferroelectric multilayer interface, thereby enhancing reflection loss and achieving a synergistic effect between semiconductor electrical loss, ferromagnetic magnetic loss, and ferroelectric dielectric loss. Furthermore, the significant difference in dielectric constant and permeability between air and Fe3O4 / BaTiO3 allows electromagnetic waves to be continuously reflected for extended periods within the high-loss Fe3O4 / BaTiO3 when entering the composite material, further enhancing absorption performance. Therefore, it exhibits excellent absorption performance even at very thin thicknesses, meeting the requirements of "thin, light, wide, and strong" for absorbing materials. At a thickness of 2.05 mm and a frequency of 13.2 GHz, the lowest reflection loss reaches -48.1 dB; at a thickness of 1.90 mm, the effective absorption bandwidth reaches 6.3 GHz.
[0051] (4) The raw materials and equipment required for the preparation method of the present invention are simple and easy to obtain, the process is simple, the cost is relatively low, and it has good economic and environmental benefits. Attached Figure Description
[0052] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:
[0053] Figure 1 These are X-ray diffraction (XRD) patterns of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite microwave absorbing material prepared in Example 1, the 0.75BaTiO3 / 0.25Fe3O4 multilayer composite microwave absorbing material prepared in Example 2, the 0.25BaTiO3 / 0.75Fe3O4 multilayer composite microwave absorbing material prepared in Example 3, the BaTiO3 powder prepared in Comparative Example 1, and the Fe3O4 powder prepared in Comparative Example 2.
[0054] Figure 2This is a scanning electron microscope (SEM) image of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite microwave absorbing material prepared in Example 1 of this invention;
[0055] Figure 3 This is a SEM image of the 0.75BaTiO3 / 0.25Fe3O4 multilayer composite microwave absorbing material prepared in Example 2 of this invention;
[0056] Figure 4 This is a SEM image of the 0.25BaTiO3 / 0.75Fe3O4 multilayer composite microwave absorbing material prepared in Example 3 of this invention. The red circle indicates the broken particles.
[0057] Figure 5 This is a SEM image of the BaTiO3 nanopowder prepared in Comparative Example 1 of this invention.
[0058] Figure 6 This is a SEM image of the Fe3O4 nanoparticles prepared in Comparative Example 2 of this invention;
[0059] Figure 7 The attenuation constants of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite microwave absorbing material prepared in Example 1, the 0.75BaTiO3 / 0.25Fe3O4 multilayer composite microwave absorbing material prepared in Example 2, the 0.25BaTiO3 / 0.75Fe3O4 multilayer composite microwave absorbing material prepared in Example 3, the BaTiO3 powder prepared in Comparative Example 1, and the Fe3O4 powder prepared in Comparative Example 2 are shown in the diagram.
[0060] Figure 8 This is a three-dimensional reflection loss diagram of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite absorbing material prepared in Example 1 of this invention;
[0061] Figure 9 This is a three-dimensional reflection loss diagram of the 0.75BaTiO3 / 0.25Fe3O4 multilayer composite absorbing material prepared in Example 2 of this invention;
[0062] Figure 10 This is a three-dimensional reflection loss diagram of the 0.25BaTiO3 / 0.75Fe3O4 multilayer composite absorbing material prepared in Example 3 of the present invention;
[0063] Figure 11 This is a three-dimensional reflection loss diagram of the BaTiO3 nanopowder prepared in Comparative Example 1 of this invention;
[0064] Figure 12 This is a three-dimensional reflection loss diagram of the Fe3O4 nanoparticles prepared in Comparative Example 2 of this invention;
[0065] Figure 13This is a three-dimensional reflection loss diagram of the 0.5BaTiO3-0.5Fe3O4 mixed powder prepared in Comparative Example 3 of this invention;
[0066] Figure 14 This is a two-dimensional reflection loss diagram of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite absorbing material prepared in Example 1 of this invention. Detailed Implementation
[0067] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0068] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0069] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0070] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0071] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0072] All raw materials used in the embodiments of this invention were obtained through commercial purchase.
[0073] The technical solution of the present invention will be further illustrated by the following embodiments.
[0074] Example 1: Preparation of 0.5BaTiO3 / 0.5Fe3O4 multilayer composite microwave absorbing material
[0075] (1) Weigh 0.9427 g (3.86 mmol) of barium chloride dihydrate (BaCl2·2H2O) and 4.8 g of sodium hydroxide (NaOH) using an electronic balance, and measure 60 mL of deionized water using a graduated cylinder. Mix the three together and stir magnetically for 30 min. Then slowly add 0.488 g (2.57 mmol) of TiCl4 dropwise to the mixed solution at a rate of 1-2 drops / second, and continue stirring magnetically for 30 min.
[0076] (2) Transfer the precursor solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 210°C for 24 hours to allow it to react fully.
[0077] (3) Wait for the oven to cool naturally, take out the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge at 8000 rpm for 2-3 minutes, wash with 3M dilute acetic acid, deionized water and alcohol in sequence, and then dry in an oven at 70℃ for 12 hours to obtain BaTiO3 nanopowder.
[0078] (4) Take 0.15g of the barium titanate nanopowder obtained in step (3) and add it to 60mL of ethylene glycol. Disperse it by ultrasonication for 30min. Then, according to the ratio of 0.5BaTiO3 / 0.5Fe3O4, add 0.5253g of ferric chloride hexahydrate (FeCl3·6H2O) and 7.2g of anhydrous sodium acetate (NaAc) and stir magnetically for 30min to obtain a yellowish-brown solution.
[0079] (5) Transfer the yellowish-brown solution obtained in step (4) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 200°C for 8 hours to allow it to react fully.
[0080] (6) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge multiple times, wash with ethanol and deionized water three times each during the process, and then dry in an oven at 70°C for 12 hours to obtain 0.5BaTiO3 / 0.5Fe3O4 multilayer composite microwave absorbing material.
[0081] Example 2: Preparation of 0.75BaTiO3 / 0.25Fe3O4 multilayer composite microwave absorbing material
[0082] (1) Weigh 0.9427g of barium chloride dihydrate (BaCl2·2H2O) and 4.8g of sodium hydroxide (NaOH) using an electronic balance, and measure 60mL of deionized water using a graduated cylinder. Mix the three together and stir magnetically for 30min. Then slowly add 0.488g of TiCl4 dropwise to the mixed solution at a rate of 1-2 drops / second, and continue stirring magnetically for 30min.
[0083] (2) Transfer the precursor solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 210°C for 24 hours to allow it to react fully.
[0084] (3) Wait for the oven to cool naturally, take out the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge at 8000 rpm for 2-3 minutes, wash with 3M dilute acetic acid, deionized water and alcohol in sequence, and then dry in an oven at 70℃ for 12 hours to obtain BaTiO3 nanopowder.
[0085] (4) Take 0.225g of the barium titanate nanopowder obtained in step (3) and add it to 60mL of ethylene glycol. Disperse it by ultrasonication for 30min. Then, according to the ratio of 0.25BaTiO3 / 0.75Fe3O4, add 0.2626g of ferric chloride hexahydrate (FeCl3·6H2O) and 7.2g of anhydrous sodium acetate (NaAc) and stir magnetically for 30min to obtain a yellowish-brown solution.
[0086] (5) Transfer the yellowish-brown solution obtained in step (4) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 200°C for 8 hours to allow it to react fully.
[0087] (6) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge multiple times, wash with ethanol and deionized water three times each during the process, and then dry in an oven at 70°C for 12 hours to obtain 0.75BaTiO3 / 0.25Fe3O4 multilayer composite microwave absorbing material.
[0088] Example 3: Preparation of 0.25BaTiO3 / 0.75Fe3O4 multilayer composite microwave absorbing material
[0089] (1) Weigh 0.9427g of barium chloride dihydrate (BaCl2·2H2O) and 4.8g of sodium hydroxide (NaOH) using an electronic balance, and measure 60mL of deionized water using a graduated cylinder. Mix the three together and stir magnetically for 30min. Then slowly add 0.488g of TiCl4 dropwise to the mixed solution at a rate of 1-2 drops / second, and continue stirring magnetically for 30min.
[0090] (2) Transfer the precursor solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 210°C for 24 hours to allow it to react fully.
[0091] (3) Wait for the oven to cool naturally, take out the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge at 8000 rpm for 2-3 minutes, wash with 3M dilute acetic acid, deionized water and alcohol in sequence, and then dry in an oven at 70℃ for 12 hours to obtain BaTiO3 nanopowder.
[0092] (4) Take 0.075g of the barium titanate nanopowder obtained in step (3) and add it to 60mL of ethylene glycol. Disperse it by ultrasonication for 30min. Then, according to the ratio of 0.25BaTiO3 / 0.75Fe3O4, add 0.788g of ferric chloride hexahydrate (FeCl3·6H2O) and 7.2g of anhydrous sodium acetate (NaAc) and stir magnetically for 30min to obtain a yellowish-brown solution.
[0093] (5) Transfer the yellowish-brown solution obtained in step (4) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 200°C for 8 hours to allow it to react fully.
[0094] (6) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge multiple times, wash with ethanol and deionized water three times each during the process, and then dry in an oven at 70°C for 12 hours to obtain 0.25BaTiO3 / 0.75Fe3O4 multilayer composite microwave absorbing material.
[0095] Comparative Example 1: Preparation of BaTiO3 Nanopowder
[0096] (1) Weigh 0.9427g of barium chloride dihydrate (BaCl2·2H2O) and 4.8g of sodium hydroxide (NaOH) using an electronic balance, and measure 60mL of deionized water using a graduated cylinder. Mix the three together and stir magnetically for 30min. Then slowly add 0.488g of TiCl4 dropwise to the mixed solution at a rate of 1-2 drops / second, and continue stirring magnetically for 30min.
[0097] (2) Transfer the precursor solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 210°C for 24 hours to allow it to react fully.
[0098] (3) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, wash and centrifuge with 3M dilute acetic acid, deionized water and alcohol in sequence, and then dry in an oven at 70℃ for 12 hours to obtain BaTiO3 nanopowder.
[0099] Comparative Example 2: Preparation of Fe3O4 Nanopowder
[0100] (1) Add 1.05g of ferric chloride hexahydrate (FeCl3·6H2O) and 7.2g of anhydrous sodium acetate (NaAc) to 60mL of ethylene glycol and stir magnetically for 30min to obtain a yellowish-brown solution.
[0101] (2) Transfer the yellowish-brown solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 200°C for 8 hours to allow it to react fully.
[0102] (3) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge at 8000 rpm for 2-3 minutes, wash with ethanol and deionized water three times each, and then dry in an oven at 70℃ for 12 hours to obtain Fe3O4 nanopowder.
[0103] Comparative Example 3: Preparation of 0.5BaTiO3-0.5Fe3O4 mixed powder
[0104] a. Preparation of BaTiO3 nanopowder:
[0105] (1) Weigh 0.9427 g of barium chloride dihydrate (BaCl2·2H2O) and 4.8 g of sodium hydroxide (NaOH) using an electronic balance, and measure 60 mL of deionized water using a graduated cylinder. Mix the three together and stir magnetically for 30 min. Then slowly add 0.488 g of TiCl4 dropwise to the mixed solution at a rate of 1-2 drops / second, and continue stirring magnetically for 30 min to obtain the precursor solution.
[0106] (2) Transfer the precursor solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 210°C for 24 hours to allow it to react fully.
[0107] (3) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, wash and centrifuge with 3M dilute acetic acid, deionized water and alcohol in sequence, and then dry in an oven at 70℃ for 12 hours to obtain BaTiO3 nanopowder.
[0108] b. Preparation of Fe3O4 nanopowder:
[0109] (1) Add 1.05g of ferric chloride hexahydrate (FeCl3·6H2O) and 7.2g of anhydrous sodium acetate (NaAc) to 60mL of ethylene glycol and stir magnetically for 30min to obtain a yellowish-brown solution;
[0110] (2) Transfer the yellowish-brown solution obtained in step (1) to a high-temperature and high-pressure reactor with a filling degree of 60% to 80%, seal the reactor, and place the reactor in an oven at 200°C for 8 hours to allow it to react fully.
[0111] (3) Wait for the oven to cool naturally, remove the reaction vessel from the oven, pour the solution into a centrifuge tube, centrifuge at 8000 rpm for 2-3 minutes, wash with ethanol and deionized water three times each, and then dry in an oven at 70℃ for 12 hours to obtain Fe3O4 nanopowder.
[0112] c. Preparation of 0.5BaTiO3-0.5Fe3O4 mixed powder:
[0113] Take 0.15g BaTiO3 and 0.15g Fe3O4 and mechanically grind them for 2 hours to obtain a 0.5BaTiO3-0.5Fe3O4 mixed powder.
[0114] The electromagnetic parameters of each material were analyzed using a Ceyear 3672B microwave vector network analyzer. The dielectric constant (ε) and permeability (μ) were measured in the 1–18 GHz range using the coaxial line method. Absorbing particles and paraffin were uniformly mixed in a 7:3 mass ratio to prepare concentric shafts with an inner diameter of 3.04 mm, an outer diameter of 7.0 mm, and a thickness of 2.0 mm for microwave absorption performance testing.
[0115] Figure 1The XRD patterns of the five products obtained in Examples 1-3 and Comparative Examples 1-2 show that 2θ = 22.20°, 31.608°, 38.91°, 45.31°, 50.96°, 56.24°, 66.01°, 70.42°, 74.99°, and 79.35° correspond to (100), (110), (111), (200), (201), (211), (220), (212), (301), and (3) of BaTiO3 (PDF#79-2264). 11) Interface; 2θ = 30.15°, 35.52°, 37.15°, 43.17°, 53.56°, 57.09°, 62.70° correspond to the (220), (311), (222), (400), (422), (511), and (440) crystal planes of Fe3O4 (PDF#88-0315); no impurity phases were observed in any of the samples, which contained only BaTO3 and Fe3O4. As the amount of Fe3O4 composite increased, the peak intensity of Fe3O4 gradually increased.
[0116] Figure 2 This is a scanning electron microscope (SEM) image of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite microwave absorbing material prepared in Example 1 of this invention. Figure 3 This is a SEM image of the 0.75BaTiO3 / 0.25Fe3O4 multilayer composite microwave absorbing material prepared in Example 2 of this invention. Figure 4 This is a SEM image of the 0.25BaTiO3 / 0.75Fe3O4 multilayer composite microwave absorbing material prepared in Example 3 of this invention. Figure 5 This is a SEM image of the BaTiO3 nanoparticles prepared in Comparative Example 1 of this invention. Figure 6 This is a SEM image of the Fe3O4 nanoparticles prepared in Comparative Example 2 of this invention. It can be seen that in the products of Examples 1-3, Fe3O4 is attached and grown on BaTiO3 particles, and the amount of Fe3O4 attached to the BaTiO3 particles gradually increases with the increase of the mass ratio. Fe3O4 was successfully loaded onto BaTiO3 using a two-step hydrothermal method. The combination of the two can adjust its impedance matching, while generating more interfaces, improving loss capacity, and contributing to the improvement of microwave absorption performance.
[0117] Besides impedance matching, the attenuation constant α is another important criterion for evaluating the electromagnetic wave absorption performance of a material, representing its overall electromagnetic wave loss performance. Generally speaking, the larger the attenuation constant, the stronger the material's ability to reduce electromagnetic waves. Figure 7This is a graph showing the attenuation constants of the 0.5BaTiO3 / 0.5Fe3O4 composite microwave absorbing material prepared in Example 1, the 0.75BaTiO3 / 0.25Fe3O4 composite microwave absorbing material prepared in Example 2, the 0.25BaTiO3 / 0.75Fe3O4 composite microwave absorbing material prepared in Example 3, the BaTiO3 powder prepared in Comparative Example 1, and the Fe3O4 powder prepared in Comparative Example 2. From... Figure 7 As can be seen, compared with other samples, especially the two single phases, 0.5BaTiO3 / 0.5Fe3O4 has a significantly improved attenuation constant, which is beneficial to the improvement of wave absorption capability.
[0118] Figure 8 This is a three-dimensional reflection loss diagram of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite absorbing material prepared in Example 1 of this invention. Figure 9 A three-dimensional reflection loss diagram of the 0.75BaTiO3 / 0.25Fe3O4 multilayer composite absorbing material prepared in Example 2 of this invention. Figure 10 This is a three-dimensional reflection loss diagram of the 0.25BaTiO3 / 0.75Fe3O4 multilayer composite absorbing material prepared in Example 3 of this invention. Figure 11 This is a three-dimensional reflection loss diagram of the BaTiO3 nanoparticles prepared in Comparative Example 1 of this invention. Figure 12 This is a three-dimensional reflection loss diagram of the Fe3O4 nanoparticles prepared in Comparative Example 2 of this invention. It can be seen that single-phase BaTiO3 has a narrow absorption bandwidth and a thick matching thickness, exhibiting virtually no absorption performance within a 4mm thickness range. This is related to the fact that BaTiO3 has almost no magnetic loss, and its dielectric loss cannot match the magnetic loss, resulting in poor impedance matching. Furthermore, the absorption loss mechanism relies solely on dielectric loss. However, with the increase in the Fe3O4 mass ratio, both the dielectric and magnetic losses of the composite material are enhanced. 0.5BaTiO3 / 0.5Fe3O4 exhibits the best absorption performance, which can be attributed to the abundant heterogeneous interfaces between BaTiO3 and Fe3O4, and the synergistic effect of dielectric and magnetic losses. While the lowest reflection loss of 0.25BaTiO3 / 0.75Fe3O4 is similar to that of 0.5BaTiO3 / 0.5Fe3O4, its bandwidth is less. This may be because the excellent absorption performance mainly comes from the synergistic effect of optimal impedance matching and attenuation loss. Although the attenuation constants of 0.25BaTiO3 / 0.75Fe3O4 are similar to those of 0.5BaTiO3 / 0.5Fe3O4, their dielectric loss and magnetic loss only meet the short-range frequency band matching, but they are mismatched in the long-range frequency range, resulting in poor overall impedance matching and a decrease in absorption performance.
[0119] Figure 13This is a three-dimensional reflection loss diagram of the 0.5BaTiO3-0.5Fe3O4 mixed powder prepared in Comparative Example 3 of this invention. It can be seen that when using traditional mechanical mixing for powder preparation, the two phases are essentially in point contact, resulting in poor overall interfacial polarization of the material and thus inferior absorption performance compared to Example 1. The optimal matching thickness is at 4.8 mm. Although the minimum reflection loss value can reach -65.7 dB, the effective absorption bandwidth is only 2.7 GHz. It is evident that the thick matching thickness and narrow effective absorption bandwidth limit its application prospects and cannot meet the current standards for "thin, light, wide, and strong" absorbing materials.
[0120] Figure 14 This is a two-dimensional reflection loss diagram of the 0.5BaTiO3 / 0.5Fe3O4 multilayer composite absorbing material prepared in Example 1 of this invention. When the thickness is 2.05 mm, the minimum reflection loss of 0.5BaTiO3 / 0.5Fe3O4 at 13.2 GHz is -48.1 dB, and the effective absorption bandwidth (EAB) reaches 4.8 GHz in the ranges of 12–15.2 GHz and 8.6–10.2 GHz. When the matching thickness is 1.9 mm, the minimum reflection loss at 9.2 GHz is -21.3 dB, and the effective absorption bandwidth (EAB) reaches 6.3 GHz in the ranges of 8.8 GHz–10.2 GHz and 12.3 GHz–17.2 GHz.
[0121] Table 1 shows the microwave absorption performance of some reported ferroelectric / ferrite composite microwave absorbing materials. It can be seen that the 0.5BaTiO3 / 0.5Fe3O4 composite material of the present invention has stronger microwave absorption capability or wider effective absorption bandwidth with a thinner coating thickness, which meets the current standard of "thin, light, wide and strong" for microwave absorbing materials and has good application prospects.
[0122] Table 1
[0123]
[0124] Note: [1]Xu, Zehao, et al. Tailoring electromagnetic wave absorption using in-situ precipitation of BaTiO3-BaFe 12 O 19 glass ceramic.Ceramics International, 2024, 50(2):3119-3128.
[0125] [2] Mandal A, Das C K. Effect of BaTiO3 on the microwave absorbingproperties of Co-doped Ni-Zn ferrite nanocomposites[J]. Journal of Applied Polymer Science, 2014, 131(4): 39926.
[0126] [3]Chen YJ, Gao P, Wang RX, et al.Porous Fe3O4 / SnO2 core / shellnanorods:synthesis and electromagnetic properties[J].The Journal of PhysicalChemistry C,2009,113(23):10061-10064.
[0127] [4]Wang Z, Wu L, Zhou J, et al.Enhanced microwave absorption of Fe3O4nanocrystals after heterogeneously growing with ZnO nanoshell[J].RS Cadvances, 2013, 3(10):3309-3315.
[0128] [5]Dong C, Zheng X, Li J, et al. Enhanced microwave magnetic properties of Ni ferrite doped ZnO[J]. IEEE transactions on magnetics, 2013, 49(7): 4238-4241.
[0129] [6] Xie Yuxi et al., Preparation method of high microwave absorption performance nano-barium titanate / iron tetraoxide hybrid material, ZL202110736189.0.
[0130] The above are merely preferred embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A method for preparing a barium titanate-based multilayer composite microwave absorbing material, characterized in that, Barium titanate nanoparticles were prepared via a hydrothermal method using BaCl2·2H2O as the barium source, TiCl4 as the titanium source, and NaOH as the mineralizing agent. The barium titanate nanoparticles were then mixed with FeCl3·6H2O and anhydrous sodium acetate to prepare a barium titanate-based composite microwave absorbing material via a hydrothermal method. The specific steps include: (1) Using BaCl2·2H2O as the barium source, TiCl4 as the titanium source, and NaOH as the mineralizing agent, add them to deionized water and mix thoroughly to obtain a precursor solution. The concentration of NaOH in the precursor solution is 2M. (2) The precursor solution was subjected to a first hydrothermal reaction. After the reaction was completed, it was naturally cooled. The solution was centrifuged, washed and dried to obtain barium titanate nanopowder. (3) The barium titanate nanopowder was ultrasonically dispersed in ethylene glycol, and then FeCl3·6H2O and anhydrous sodium acetate were added and stirred to obtain a yellowish-brown solution; (4) The yellowish-brown solution is subjected to a second hydrothermal reaction. After the reaction is completed, the solution is naturally cooled, and after centrifugation, washing and drying, barium titanate-based composite microwave absorbing material is obtained. In step (3), the barium titanate nanopowder and FeCl3·6H2O are mixed in the form of (1-x)BaTiO3-xFe3O4, where 0.25≤x≤0.
75.
2. The method for preparing the barium titanate-based multilayer composite microwave absorbing material according to claim 1, characterized in that, In step (1), the molar ratio of BaCl2·2H2O to TiCl4 is 1.5∶1.
3. The method for preparing the barium titanate-based multilayer composite microwave absorbing material according to claim 1, characterized in that, In step (2), the first hydrothermal reaction is carried out in a reactor with a filling degree of 60-80%, a temperature of 210°C, and a time of 24 hours.
4. The method for preparing the barium titanate-based multilayer composite microwave absorbing material according to claim 1, characterized in that, In step (2), the centrifugation is performed in a centrifuge with a speed of 7000~9000 rpm for 2~3 minutes; The washing process involves sequentially washing with dilute acetic acid, deionized water, and ethanol. The drying process involved drying in an oven at 70°C for 12 hours.
5. The method for preparing the barium titanate-based multilayer composite microwave absorbing material according to claim 1, characterized in that, In step (3), the ultrasonic time is 30 min; the stirring time after adding FeCl3·6H2O and anhydrous sodium acetate is 30 min.
6. The method for preparing the barium titanate-based multilayer composite microwave absorbing material according to claim 1, characterized in that, In step (4), the second hydrothermal reaction is carried out in a reactor with a filling degree of 60-80%, a temperature of 200°C, and a time of 8 hours.
7. A barium titanate-based multilayer composite microwave absorbing material, characterized in that, It is prepared according to any one of claims 1 to 6.
8. The application of the barium titanate-based multilayer composite absorbing material according to claim 7 in the fields of stealth aircraft, electromagnetic interference, and radiation protection clothing.
Citation Information
Patent Citations
Preparation method of nano barium titanate / ferroferric oxide hybrid material with high wave-absorbing performance
CN113329608A